Descriptive Analysis of the Graphic Representations of Science Textbooks - Myint Swe Khine; Yang Liu (Lectito Journals, 2017)
Textbooks are primary teaching aids, sources from which students obtain knowledge of science domain. Due to this fact, curriculum developers in the field emphasize the crucial role of analysing the contents of science textbooks in improving science education. Scientific domain knowledge relies on graphical representations for the manifestation of itself. Content analysis of the representations therefore entails the necessity of the systematic reading and categorizing of a body of visual representations, including diagrams, drawings, photos, and text that appeared in these science teaching and learning materials. This paper examined ten UAE primary science textbooks and practical books using an author-improved graphical analysis grid. From the descriptive analysis, it was found that general science was the illustrated topic area for fundamental level of science. The most frequently used graphical type is the iconic. Female images outnumber the male images. Results also showed that indigenous graphics were dominant over foreign graphics. The study also found the majority of visual representations in the textbooks were designed to convey static information and they are in close relationship with the textual representations. Yet most of the graphical images were indexed and captioned that served specific cognitive functions. The results also suggest graphic representations need to be treated as an important visual tool that textbook authors should use them wisely to have the domain knowledge conveyed in various topic areas.